Soft chemistry routes for the preparation of Ag-CoFe2O4 nanocomposites. Issue 3 (15th February 2017) - Gingasu, Dana; Mindru, Ioana; Patron, Luminita; Marinescu, Gabriela; Preda, Silviu; Calderon-Moreno, Jose Maria; Osiceanu, Petre; Somacescu, Simona; Stanica, Nicolae; Popa, Marcela; Saviuc, Crina; Chifiriuc, Mariana Carmen
Abstract: Silver-cobalt ferrite nanocomposites (Ag-CoFe2 O4 ) were synthesized through wet ferritization process and self-propagating combustion method. The structure, morphology, surface chemistry and magnetic properties of the nanocomposites were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR) and vibrating sample magnetometer (VSM). X-ray diffraction patterns confirmed the formation of CoFe2 O4 and Ag nanoparticles with cubic symmetry. The average crystallite size of CoFe2 O4 by wet ferritization ranged between 60 Å and 87 Å; for those obtained by self-propagating combustion was in the range 232–290 Å. SEM micrographs revealed different morphological features of nanocomposites. Ag-CoFe2 O4 obtained by wet ferritization exhibited typical superparamagnetic behaviour. The antimicrobial and anti-biofilm properties of all silver-cobalt ferrites were evaluated. The results revealed that the Ag-CoFe2 O4 nanocomposites exhibited good microbicidal and anti-biofilm features.